2013
DOI: 10.2528/pier12102510
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Radiated Electromagnetic Emissions of Electric Motorcycles in Terms of Driving Profile Using MLP Neural Networks

Abstract: Abstract-Current automotive electromagnetic compatibility (EMC) standards do not discuss the effect of the driving profile on real traffic vehicular radiated emissions. This paper describes a modeling methodology to evaluate the radiated electromagnetic emissions of electric motorcycles in terms of the driving profile signals such as the vehicle velocity remotely controlled by means of a CAN bus. A time domain EMI measurement system has been used to measure the temporal evolution of the radiated emissions in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For that reason, an alternative approach based on artificial neural networks (ANNs) has been proposed in this paper. Neural networks are very convenient as a modeling tool since they have the ability to learn from presented data [17][18][19][20][21]. Compared to conventional signal processing algorithms that are mainly based on linear models, neural networks consider DOA estimation as approximation of highly nonlinear multidimensional function, or in other words, as a mapping between spatial covariance matrix of received signals from antenna elements and DOAs.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, an alternative approach based on artificial neural networks (ANNs) has been proposed in this paper. Neural networks are very convenient as a modeling tool since they have the ability to learn from presented data [17][18][19][20][21]. Compared to conventional signal processing algorithms that are mainly based on linear models, neural networks consider DOA estimation as approximation of highly nonlinear multidimensional function, or in other words, as a mapping between spatial covariance matrix of received signals from antenna elements and DOAs.…”
Section: Introductionmentioning
confidence: 99%
“…In order to bypass the difficulties of inverting a numerical model to estimate these parameters starting from EC data [18], a model-free estimation technique based on the use of an ANN is considered. This kind of approach has been proven to be efficient in various modeling and estimation problems in the electromagnetic domain [19,20]. In this study, a feed-forward neural network (FFNN) is implemented to estimate the conductivity variations [21].…”
Section: Evaluation Of Conductivity Variation Of Aluminum and Solder mentioning
confidence: 99%
“…Furthermore, such antenna would receive a lot of radiated waves from various interfering sources like: other vehicles, WiFi, GPS, Bluetooth, television broadcast, radio broadcast, mobile networks, satellite networks, and power lines. In previous articles [17,18], authors have already proposed a procedure of three steps to solve this problem as shown in Figure 1. In this paper, the same methodology has been applied on a Renault Twizy and a Think City.…”
Section: Introductionmentioning
confidence: 99%